2018
DOI: 10.1080/19396368.2018.1450460
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed procyanidins extract attenuates Cisplatin-induced oxidative stress and testosterone synthase inhibition in rat testes

Abstract: CIS: Cisplatin; GSPE: grape seed procyanidins extract; LH: luteinizing hormone; FSH: follicle-stimulating hormone; STAR: steroidogenic acute regulatory protein; CYP11A1: P450 side chain cleavage enzyme; HSD3B1: 3β-hydroxysteroid dehydrogenase; CYP17A1: 17α-hydroxylase; HSD17B: 17β-hydroxysteroid dehydrogenase; ROS: reactive oxygen species; O2: superoxide anion; HO: hydrogen peroxide; •OH: hydroxyl radicals; SOD: superoxide dismutase; CAT: catalase; GSH-Px: glutathione peroxidase; LPO: lipid peroxidation; 8-OHd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 54 publications
1
31
0
Order By: Relevance
“…However, the testosterone changes across all groups were not statistically significant. Other studies, of longer duration (Reddy, Madhu, & Reddy, ), or using a higher cisplatin dose (Tian et al., ) have documented a clear decrease in testicular weight and circulating testosterone in response to cisplatin treatment. It is therefore likely that these parameters required a longer study duration or higher dosage to become pronounced in our model.…”
Section: Discussionmentioning
confidence: 95%
“…However, the testosterone changes across all groups were not statistically significant. Other studies, of longer duration (Reddy, Madhu, & Reddy, ), or using a higher cisplatin dose (Tian et al., ) have documented a clear decrease in testicular weight and circulating testosterone in response to cisplatin treatment. It is therefore likely that these parameters required a longer study duration or higher dosage to become pronounced in our model.…”
Section: Discussionmentioning
confidence: 95%
“…The sequences of primers were designed and synthesized by Sangon Biotechnology Co., Ltd. (Shanghai, China) and listed in Table 1. Formula 2^ (−ΔΔCt) was used to calculate the fold change of gene expression (Tian et al., 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In this context, work has revealed that the GSSE can protect against oxidative stress thanks to its power to trap ROS [4]. Even; Tian et al, (2018) [24] have shown that grape extracts have the ability to mitigate oxidative stress and to protect against inhibition of testosterone synthetase caused by cisplatin in the testes. Regarding U. rigida, previous work is done in our laboratory clearly demonstrate that this seaweeds possess a strong antioxidant power linked to the richness of its extracts in proteins, in compounds, phenolic and polysaccharides known for their remarkable antioxidant capacities [3,12].…”
Section: Resultsmentioning
confidence: 99%